PERENCANAAN LANSKAP WISATA PANTAI TANJUNG BARU BERBASIS ECO-LANDFORM - Afra D.N. Makalew; Vera D. Damayanti; Juniar Adi Nugraha (http://arl.faperta.ipb.ac.id/, 2013)
ABSTRACTBeach landform is geographically formed by sand and located in sea shore. Land use change of mangrove forest into embankment and the development of tourism in Tan-jung Baru Beach has lead to the occurrence of enviromental degradation in this area. This research was aimed to identify and analyze bio-physical condition, and also to propose landscape planning concept and development toward the ecologycal landform based tourism planning. The method used in this research refers to ecological approach with the planning stages by Gold (1980). That method consists of preparation, inven-tory, analysis, synthesis, and landscape planning. Descriptive and spatial analyze were used to determine the quality ecology and tourism aspects. Spatial analysis of these aspects is use to determine the quality of ecology and tourism area of Tanjung Baru Beach. The result of this research shows that there are 4 quality categories of ecology aspect which are worst, less, rare, and good. The tourism aspect found that the category is the same as in ecology aspect. The proposed recommendation is focused on conservation and rehabilition of mangrove forest as ecological based tourism planning.Keywords: Ecology, Landform, Beach, Tourism, Landscape Planning